1981
DOI: 10.1172/jci110110
|View full text |Cite
|
Sign up to set email alerts
|

Healing of rickets with phosphate supplementation in the hypophosphatemic male mouse.

Abstract: A B S T R A C T The hypophosphatemic male mouse, an animal model for human vitamin D-resistant rickets, is characterized by low serum phosphorus concentration due to increased urinary phosphate excretion, rickets, osteomalacia, and dwarfism. Because phosphate administration can heal rickets but not osteomalacia in the human disease, we have compared the effect of phosphate supplementation on the epiphyseal and endosteal bone mineralization in the mutant animal. Phosphate was given in drinking water for 137

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
26
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 12 publications
8
26
0
Order By: Relevance
“…Several identical mutations including R291X were observed in different ethnic populations (19,21,22). Moreover, the frequency of de novo mutations has been estimated as approximately 20% (15,16,18). These findings suggest that the PHEX gene appears to be particularly prone to mutations for unknown reasons.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several identical mutations including R291X were observed in different ethnic populations (19,21,22). Moreover, the frequency of de novo mutations has been estimated as approximately 20% (15,16,18). These findings suggest that the PHEX gene appears to be particularly prone to mutations for unknown reasons.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the mRNA of PHEX in human fetal tissue has been found to be preferentially expressed in early bone development (9). In the hypophosphatemic (Hyp) mouse model of XLH, the murine phosphate-regulating gene (Pex) mRNA expression is also seen mainly in bone (9), and bone formation is not normalized after transplantation of bone cells from Hyp mice into the normal mice (15)(16)(17)(18). These findings indicate that PHEX protein not only has endopeptidase-like function, but is also important for bone formation (9,(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Inefficient re-absorption of phosphate by the kidney is associated with defective mineralization of the skeleton, which manifests as rickets in children and osteomalacia in adults. High doses of oral phosphate have been shown to be as effective as vitamin D in healing rachitic lesions in humans (15), as well as in rats (16) and mice (17). By adapting micropuncture techniques to sample cartilage lymph in the growth plates of rachitic rats, it was shown that phosphate is preferentially sequestered relative to calcium in the zone of hypertrophic cells surrounded by unmineralized cartilage (18).…”
mentioning
confidence: 99%
“…The defective renal phosphate transport in Hyp mice (3) has been attributed to decreased renal expression of the Na-Pi cotransporter gene and immunoreactive protein (4) and is thought to result from the effect of a humoral factor (5,6). The failure of phosphate therapy and the need for concurrent administration of supraphysiological doses of 1,25-(OH) 2 D 3 to correct the bone osteomalacic lesions in affected patients (7,8) and mice (9,10) have indicated that hypophosphatemia is not the sole cause of the defective bone mineralization. Evidence has been provided for an associated osteoblast dysfunction in this disorder.…”
mentioning
confidence: 99%